Experimental investigation of fibre reinforced plastics with hybrid layups under high-velocity impact loads - Marco Romano; Carl J. J. Hoinkes; Ingo Ehrlich; Johann Höcherl; Norbert Gebbeken (Fracture and Structural Integrity)
This paper deals with experimental investigations concerning energy dissipation capacity of different kinds of reinforcement fibres in monolithic and hybrid layups under high-velocity impact loads. The investigated kinds of fibres are carbon, glass and basalt fibres. Therefore test panels, using the same thermoset resin, were built up and cured by autoclave processing. The fibre volume content of the test panels has been determined. Furthermore the influence of a separating layer at selected positions in the hybrid stacked panels was investigated. The results show the influence and the energy dissipation capacity of each single kind of fibre and the enhanced properties for the hybrid layups by hybrid stacking sequences and the use of a separating core material.